N-Acetylglucosamine Inhibits LuxR, LasR and CviR Based Quorum Sensing Regulated Gene Expression Levels - Kimyon, Önder; Ulutürk, Zehra İ. and Nizalapur, Shashidhar and Lee, Matthew and Kutty, Samuel K. and Beckmann, Sabrina and Kumar, Naresh and Manefield, Mike (Frontiers in Microbiology, 2016)
N-acetyl glucosamine, the monomer of chitin, is an abundant source of carbon and nitrogen in nature as it is the main component and breakdown product of many structural polymers. Some bacteria use N-acyl-L-homoserine lactone (AHL) mediated quorum sensing (QS) to regulate chitinase production in order to catalyze the cleavage of chitin polymers into water soluble N-acetyl-D-glucosamine (NAG) monomers. In this study, the impact of NAG on QS activities of LuxR, LasR, and CviR regulated gene expression was investigated by examining the effect of NAG on QS regulated green fluorescent protein (GFP), violacein and extracellular chitinase expression. It was discovered that NAG inhibits AHL dependent gene transcription in AHL reporter strains within the range of 50–80% reduction at low millimolar concentrations (0.25–5 mM). Evidence is presented supporting a role for both competitive inhibition at the AHL binding site of LuxR type transcriptional regulators and catabolite repression. Further, this study shows that NAG down-regulates CviR induced violacein production while simultaneously up-regulating CviR dependent extracellular enzymes, suggesting that an unknown NAG dependent regulatory component influences phenotype expression. The quorum sensing inhibiting activity of NAG also adds to the list of compounds with known quorum sensing inhibiting activities.